2019
DOI: 10.3390/su11143881
|View full text |Cite
|
Sign up to set email alerts
|

Just Transformations to Sustainability

Abstract: Transformations towards sustainability are needed to address many of the earth's profound environmental and social challenges. Yet, actions taken to deliberately shift social-ecological systems towards more sustainable trajectories can have substantial social impacts and exclude people from decision-making processes. The concept of just transformations makes explicit a need to consider social justice in the process of shifting towards sustainability. In this paper, we draw on the transformations, just transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
122
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(152 citation statements)
references
References 140 publications
0
122
0
Order By: Relevance
“…At the same time, history has shown that past coal transitions have often had severe negative socioeconomic consequences on the affected regions due to poor management [1]. Consequently, literature has put an increasing focus on the just transition towards sustainable social-ecological systems [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, history has shown that past coal transitions have often had severe negative socioeconomic consequences on the affected regions due to poor management [1]. Consequently, literature has put an increasing focus on the just transition towards sustainable social-ecological systems [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…But these indicators cannot identify why target goals have not been accomplished, whether or how they do or do not do justice to the social and cultural context in which they are applied, and how newly emerging social dynamics affect indicators. Nor do they provide means for resolving conflicting values and making balanced trade-offs [9][10][11].…”
Section: Insufficiency Of Sustainability Indicatorsmentioning
confidence: 99%
“…For example, when conflicts over how to allocate the costs of mitigating climate change stall negotiation, increasing costs for all, the impasse can be overcome by explicit appeal to fairness (Gampfer, 2014). This sense of fairness is a common theme in discussions of environmental equity and justice (Bennett, Blythe, Cisneros-Montemayor, Singh, & Sumaila, 2019)-often supporting the underdog in disputes over the allocation of environmental costs and benefits-and arguably underpins the call to give animals equal rights (Regan & Singer, 1989). Indeed, the Nature Needs Half campaign (natureneedshalf.org) makes an explicit appeal to fairness when advocating that, to reduce anthropogenic stress on biodiversity, people allocate to nonhumans an equal share of land and energy flows.…”
Section: Fair Sharesmentioning
confidence: 99%